PENGARUH VARIASI LATIHAN HURDLE JUMP TERHADAP LOMPATAN PENJAGA GAWANG DI KLUB SEPAK BOLA MANDAU PUTRA KETAPANG - Gregorius Tigor Malau; Mimi Haetami; Andika Triansyah (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2022)
AbstrakResearch on the effect of the hurdle jump exercise variation is one of the variations practice for goalkeepers. This research was conducted because researchers feel that the goalkeeper, especially at the Mandau Putra club, is very lacking in terms of jumps with the intention of being more efficient in increasing with tempo short ones. This study aims to improve the ability of guards goal, namely increasing the jump with a variation of the hurdle jump exercise on the goalkeeper at Mandau men's club. This study uses the analysis of quantitative descriptive with experimental and design research methods The study used one group pre-test-post-test design and used The research instrument is the vertical jump test with eight jump tools hurdle jump exercise. The subject of this research is the goalkeeper at the club Mandau Putra located in Ketapang Regency, with a total of 3 people. Based on The results of this study can be concluded that there is an influence from the variation of hurdle exercises jump against the jump of the goalkeeper Mandau Putra with a significant increase obtained by 7 cm the ability to jump with a vertical jump test instrument after being given treatment 12 times meeting.Keywords: Goalkeeper, Hurdle Jump, Leap